Synthesis, biological evaluation and molecular docking of N, N'-bis([1, 2, 4]triazole[4, 3-b][1, 2, 4, 5]tetrazine-6-yl)alkylamine derivatives as potent c-Met antagonists. Issue 5 (September 2022) - Ke, Zhonglu; Pei, Tianyun; Yang, Zhenzhen; Zhang, Xuanhe; Xu, Feng; Xu, Zihang; Ding, Jixiang
A series of N, N '-bis([1, 2, 4]triazole[4, 3- b ][1, 2, 4, 5]tetrazine-6-yl)alkylamine derivatives is designed, synthesized and evaluated for their inhibition activities against three tumor cell lines and c-Met kinase activity in vitro . These compounds are fully characterized by 1 H NMR, 13 C NMR, MS, IR and elemental analysis. Antitumor experiments indicate that some of these compounds exhibit significant inhibition activities against A549, Bewo and MCF-7 cancer cell lines. Among them, the IC50 values of4a indicate better antitumor activities against the A549 (1.21 μM), Bewo (0.68 μM) and MCF-7 (3.74 μM) cell lines than the positive agent cisplatin (9.97 μM for A549, 10.46 μM for Bewo, and 15.03 μM for MCF-7), respectively.